EFFECT OF ANTHROPOGENIC ACTIVITIES ON PERIPHYTON ALGAL ASSOCIATION OF NWANIBA RIVER - Mukoro, Denise; Asuquo, G. V.; Effiong, I. E.; Solomon, N.; Akpan, M. C.; Gabriel, C. A.; Archibong, R. S.; Hogan, P. O.; Ukwe, M. U.; Udoh, S. E.; Obop, D. D.; Dominic, R .P.; et al. (FUDMA Journal of Sciences, 2026)
Freshwater ecosystems are increasingly threatened by anthropogenic activities that alter their physicochemical and biological integrity. This study investigated the impact of human activities on the physicochemical parameters and periphyton community of the Nwaniba River, Akwa Ibom State, Nigeria. Water samples were collected from three stations along the river—upstream (control), midstream (domestic waste influence), and downstream (agricultural and light industrial influence). Standard methods were employed to assess parameters including pH, dissolved oxygen, turbidity, conductivity, temperature, and nutrient levels, while periphyton samples were analyzed for composition, abundance, and diversity. Results showed that Bacillariophyta (47.4%) dominated the algal community, indicating relatively good water quality, while Chlorophyta (31.6%) reflected nutrient enrichment and early eutrophication linked to domestic and agricultural inputs. Charophyta (15.8%) suggested the presence of clean and oxygen-rich sections, whereas low Euglenophyta abundance (5.3%) indicated minimal organic pollution. Overall, findings reveal that while the Nwaniba River retains some ecological balance, increasing anthropogenic pressures are altering its water quality and periphyton structure, posing risks of progressive degradation if unmanaged.
Keywords: Nwaniba River; Anthropogenic Activities; Physicochemical Parameters; Periphyton; Sustainable Management